Confining legitimacy: the impact of prison experiences on perceptions of criminal justice legitimacy - Smoyer, Amy B; Kershaw, Trace; Blankenship, Kim M (Journal of forensic social work, 2015)
Keywords: dept.swk

Recent Intimate Partner Violence, Sexual Risk and HIV-Related Worry: Examining the Mediating Effects of Sexual Autonomy - Willie, Tiara; Callands, Tamora; Phillips, Karlye; Flowers, Bianca; Kershaw, Trace (Sexuality Research and Social Policy, 2025)
Keywords: Anxiety; Autonomy; Clinical psychology; Criminology; Domestic violence; Environmental health; HIV; Intimate partner violence; Medicine; Poison control; Political science; Population; Psychiatry; Psychology; Reproductive health; Sexual health; Sexual violence; Suicide prevention; Worry; dept.pch

Intersectional experiences of discrimination in a low-resource urban community: An exploratory latent class analysis - Earnshaw, Valerie A.; Rosenthal, Lisa; Gilstad-Hayden, Kathryn; Carroll-Scott, Amy; Kershaw, Trace S.; Santilli, Alycia; Ickovics, Jeannette R. (Journal of Community and Applied Social Psychology, 2018)
There have been increasing calls for the application of an intersectionality framework to understand and address discrimination and health inequities among diverse communities. Yet there have been theoretical debates regarding to whom intersectionality applies and how intersectional experiences of discrimination are associated with health outcomes. The current study aimed to contribute to these theoretical debates and inform practical applications to reduce health inequities. Data were drawn from a community health survey in New Haven, CT (N=1,293 adults) and analysed using latent class analysis. Results yielded 4 classes. Members of the 4 classes were similar sociodemographically. Three classes of participants reported experiencing discrimination, and members of these classes had greater stress, higher rates of smoking and sleep disruption, and worse overall health than members of the class reporting no discrimination. Members of 2 classes made multiple, or intersectional, attributions for discrimination, and members of these classes reported the most frequent discrimination. Findings suggest that community members who are sociodemographically similar may have diverse discrimination experiences. Multilevel interventions that address multiple forms of discrimination (e.g., racism and sexism) may hold promise for reducing discrimination and, ultimately, health inequities within low-resource urban community settings.
Keywords: adult; article; dept.pch; discrimination; female; health inequities; human; human experiment; intersectionality; latent class analysis; major clinical study; male; peer-reviewed; public health; racism; sexism; sleep; smoking; stress; theoretical study; urban population